Online Teaching at the Universidad Veracruzana: Emerging Strategies and Challenges - María del Pilar Ortiz Lovillo; Daniel Jacobo Gidi Martí (University of Belgrade, Teacher Education Faculty, 2021)
In this paper, we briefly dissert past pandemics throughout history before addressing Covid-19. The objective is to describe the effects it has had on higher education and especially language, translation, and research teaching, as well as the challenges that have been faced with shifting from face-to-face lessons to online learning with help from information technologies. The advantages and disadvantages of this educational approach in a postgraduate context are reviewed, and the solutions that had to be implemented to offer quality education and avoid negative consequences for students' learning. This project explains the strategies applied by the authorities, professors, and students at the Universidad Veracruzana. It is a qualitative interpretative study in which the data was collected through semi-structured interviews. The most interesting findings were the writing and speaking improvements of the students, given the thorough review from their professors and peers. Moreover, they learned to construct their knowledge and become more autonomous in search of solutions to the problems during confinement. At the same time, the professors learned to operate multiple e-learning platforms so as not to stay behind. In conclusion, all involved learned to be more resilient and positively look at life, despite the obstacles.